Integrating protein homeostasis strategies in prokaryotes - Mogk, Axel; Huber, Damon; Bukau, Bernd (Cold Spring Harbor perspectives in biology, 2011)
Bacterial cells are frequently exposed to dramatic fluctuations in their environment, which cause perturbation in protein homeostasis and lead to protein misfolding. Bacteria have therefore evolved powerful quality control networks consisting of chaperones and proteases that cooperate to monitor the folding states of proteins and to remove misfolded conformers through either refolding or degradation. The levels of the quality control components are adjusted to the folding state of the cellular proteome through the induction of compartment specific stress responses. In addition, the activities of several quality control components are directly controlled by these stresses, allowing for fast activation. Severe stress can, however, overcome the protective function of the proteostasis network leading to the formation of protein aggregates, which are sequestered at the cell poles. Protein aggregates are either solubilized by AAA+ chaperones or eliminated through cell division, allowing for the generation of damage-free daughter cells.
Gesehen am 01.09.2022